The Earth BioGenome project: opportunities and challenges for plant genomics and conservation. (29th January 2020) - Exposito‐Alonso, Moises; Drost, Hajk‐Georg; Burbano, Hernán A.; Weigel, Detlef
Summary: Sequencing them all . That is the ambitious goal of the recently launched Earth BioGenome project (Proceedings of the National Academy of Sciences of the United States of America, 115, 4325–4333), which aims to produce reference genomes for all eukaryotic species within the next decade. In this perspective, we discuss the opportunities of this project with a plant focus, but highlight also potential limitations. This includes the question of how to best capture all plant diversity, as the green taxon is one of the most complex clades in the tree of life, with over 300 000 species. For this, we highlight four key points: (i) the unique biological insights that could be gained from studying plants, (ii) their apparent underrepresentation in sequencing efforts given the number of threatened species, (iii) the necessity of phylogenomic methods that are aware of differences in genome complexity and quality, and (iv) the accounting for within‐species genetic diversity and the historical aspect of conservation genetics. Significance Statement: The Earth BioGenome project aims to sequence and produce reference genomes for all eukaryotic species on Earth. What biological insights do we gain from sequencing? What plant species should we sequence? Are there any foreseeable challenges? Is this the right time to sequence all species? In this Perspectives article, we address these questions and study the opportunities and challenges of the Earth BioGenome project for plant genomics and conservation.